New species and records of Caulleriella, Chaetocirratulus and Chaetozone (Annelida, Cirratulidae) from continental shelf and slope depths of the Western North Atlantic Ocean - Blake, James A. (Zootaxa, 2022)
Seventeen species of cirratulid polychaetes, 13 new to science, are reported from continental shelf and slope depths of the western North Atlantic Ocean. The samples were collected as part of deep-water offshore reconnaissance surveys from New England to the Carolinas and long-term monitoring programs in Boston Harbor, Massachusetts Bay, and Georges Bank off Massachusetts. The new species are included in the genera Caulleriella (C. cryptica n. sp.), Chaetocirratulus (C. hessleri n. sp., C. sandersi n. sp., and C. tomaculus n. sp.), and Chaetozone (C. adunca n. sp., C. artaspinosa n. sp., C. brychiata n. sp., C. castouria n. sp., C. donerae n. sp., C. lophia n. sp., C. novagracilis, n. sp., C. paucispinosa n. sp. and C. profunda n. sp. In addition, Chaetozone gayheadia Hartman, 1965 is redescribed based on type-material and additional collections and transferred to the genus Chaetocirratulus. Chaetozone benthaliana McIntosh, 1985 is designated a species inquirendum because it was described from a posterior fragment that cannot be confirmed as belonging to any known cirratulid genus or species. Updated descriptions and new records are provided for Chaetozone anasima, C. diodonta, and C. hystricosa all originally described by Doner & Blake (2006).